2016
DOI: 10.3389/fnhum.2016.00378
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Effect of Basic Emotions on Directed Forgetting? Investigating the Role of Basic Emotions in Memory

Abstract: Studies presenting memory-facilitating effect of emotions typically focused on affective dimensions of arousal and valence. Little is known, however, about the extent to which stimulus-driven basic emotions could have distinct effects on memory. In the present paper we sought to examine the modulatory effect of disgust, fear, and sadness on intentional remembering and forgetting using widely used item-method directed forgetting (DF) paradigm. Eighteen women underwent fMRI scanning during encoding phase in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 96 publications
2
16
1
Order By: Relevance
“…For example, disgusting stimuli enhance episodic memory and seem to have a special salience in memory relative to other equally arousing and negative emotions, such as fear9394. Moreover, a recent fMRI study found that disgusting stimuli were the hardest to forget compared to fearful and sad stimuli, and increased amygdala activity along with the hippocampus95.…”
Section: Discussionmentioning
confidence: 99%
“…For example, disgusting stimuli enhance episodic memory and seem to have a special salience in memory relative to other equally arousing and negative emotions, such as fear9394. Moreover, a recent fMRI study found that disgusting stimuli were the hardest to forget compared to fearful and sad stimuli, and increased amygdala activity along with the hippocampus95.…”
Section: Discussionmentioning
confidence: 99%
“…When semantic relatedness is controlled, there is no evidence for increased false alarms for emotional pictures (Choi et al, 2013). Consideration of discrete emotions may also be important as hits and false alarm rates can differ across discrete emotions, such as disgust, fear, and sadness (Marchewka et al, 2016).…”
Section: Emotional Stimuli Are Semantically Inter-relatedmentioning
confidence: 99%
“…This effect was most pronounced in the case of disgust. Recent studies have already shown that stimuli eliciting disgust are able to capture and hold our attention much more effectively than fear-evoking images (Van Hooff et al, 2013 ; van Hooff et al, 2014 ) and are better remembered after a short retention period (Croucher et al, 2011 ; Marchewka et al, 2016 ). However, it is still debated whether disgust, since it is evidently a basic sensory affect (Rozin and Fallon, 1987 ) as well as a socially constructed moral emotion (Haidt, 2003 ), should be classified as a basic emotion (for discussion see Panksepp, 2007 ; Toronchuk and Ellis, 2007 ; Panksepp and Watt, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the neuronal level, using fMRI and the directed forgetting paradigm, it was revealed that correctly recognized disgusting stimuli evoked the highest activity in the left amygdala compared to all other categories. This structure was also more activated for remembered vs. forgotten stimuli, but only in case of disgust or fear eliciting pictures (Marchewka et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%